2016
DOI: 10.20547/jms.2014.1603101
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Relationship between Urbanization, Energy Consumption and Environmental Degradation in Pakistan: Evidence from Structure Break Testing

Abstract: This study investigates the Carbon dioxide emission-urbanization-growth nexus in Pakistan by taking time series data from the period of 1972 to 2013. The study applied three approaches of co-integration (ARDL bounds test, Johansen and Juselius and Gregory and Hansen structural break test) to confirm the valid long-run positive interaction between carbon dioxide emission and urbanization. The robustness of cointegrating vectors are further checked using FMOLS and DOLS tests and the results validate the long-run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 40 publications
(47 reference statements)
0
25
0
2
Order By: Relevance
“…In recent years, there has been a prominent and rapid growth in urbanization worldwide. In 2010, the world population in urban centers reached up to 50% . Generally, urbanization is considered the pillar of a prosperous economy, but its effects on the environment and infrastructure are of great concern to the policymakers, as it has been found that urbanization has increased energy use, carbon emissions and depletion of natural resources.…”
Section: Overview Of Sectorial Ghg Emissions In Pakistanmentioning
confidence: 99%
“…In recent years, there has been a prominent and rapid growth in urbanization worldwide. In 2010, the world population in urban centers reached up to 50% . Generally, urbanization is considered the pillar of a prosperous economy, but its effects on the environment and infrastructure are of great concern to the policymakers, as it has been found that urbanization has increased energy use, carbon emissions and depletion of natural resources.…”
Section: Overview Of Sectorial Ghg Emissions In Pakistanmentioning
confidence: 99%
“…Renewable assets, on the other hand, such as hydropower, solar, biomass, wind, and geothermal, also have direct environmental impacts and influences -some of which are favorable (Sekrafi & Sghaier, 2018). According to Sharif and Raza (2016), the right dimension and degree of environmental impacts varies depending on certain technological processes, geographic locations, and several other variables and factors. In OECD nations, the environmental impact of energy harvesting and consumption is diverse.…”
Section: Energy Consumption and Environmental Degradationmentioning
confidence: 99%
“…ARDL approach has preference over other cointegration methods because ARDL can be used regardless of whether selected variables are stationary at I(0), I(1) or mutually co-integrated (Pesaran & Shin, 1998). The ARDL method has better estimated for small sample properties (Haug, 2002;Shah, 2016;Sharif, Raza, et al, 2016). Regardless explanatory variable is endogenous even then in ARDL method, the estimations may be performed (Pesaran & Shin, 1998;Pesaran et al, 2001Pesaran et al, , 2001).…”
Section: Cointegration Analysismentioning
confidence: 99%